Modified carbon fibers with surface loaded polyimide interface layer, and methods of making and using the same

CN122879983APending Publication Date: 2026-10-09CHANGCHUN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611073791.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了解决现有水性聚酰胺酸盐上浆层直接热亚胺化过程中易发生涂层迁移、微孔和裂纹形成、有机胺盐残留较高以及湿热稳定性不足等问题,从而提供一种表面负载聚酰亚胺界面层的改性碳纤维及其制备方法和应用,该方法在碳纤维表面形成水性聚酰胺酸盐(PAAS)上浆层;在热亚胺化前,使PAAS上浆层与挥发性有机酸水溶液或其蒸气接触,发生原位质子交换,使至少部分PAAS转化为水难溶性的聚酰胺酸(PAA),形成预固定PAA层;经低温干燥降低游离水分、残余挥发性有机酸、有机胺盐及可迁移小分子残留;再经分段升温热亚胺化形成聚酰亚胺(PI)界面层

Benefits of technology

1、本发明在碳纤维表面形成水性聚酰胺酸盐(PAAS)上浆层;在热亚胺化前,使PAAS上浆层与挥发性有机酸水溶液或其蒸气接触,发生原位质子交换,使至少部分PAAS转化为水难溶性的聚酰胺酸(PAA),形成预固定PAA层;经低温干燥降低游离水分、残余挥发性有机酸、有机胺盐及可迁移小分子残留;再经分段升温热亚胺化形成聚酰亚胺(PI)界面层。将水性聚酰胺酸盐的水性输送、碳纤维表面原位固定和热亚胺化过程解耦,避免了水性聚酰胺酸盐上浆层在升温初期因仍具有水溶性和离子性而发生明显迁移。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879983A_ABST
    Figure CN122879983A_ABST
Patent Text Reader

Abstract

The application provides a modified carbon fiber with a surface loaded polyimide interface layer and a preparation method and application thereof, and belongs to the technical field of water-based polyimide sizing preparation. The method forms a water-based polyamide acid salt (PAAS) sizing layer on the surface of the carbon fiber; before thermal imidization, the PAAS sizing layer is contacted with a volatile organic acid aqueous solution or steam to occur in-situ proton exchange, so that at least part of the PAAS is converted into water-insoluble polyamide acid to form a pre-fixed PAA layer; low-temperature drying is performed to reduce free moisture, residual volatile organic acid, organic amine salt and migratable small molecule residues; and then, segmented heating thermal imidization is performed to form a polyimide interface layer. The water-based delivery, interface fixation and thermal imidization process are decoupled, the coating migration, pore and crack formation can be inhibited, the interface bonding strength of the carbon fiber / thermoplastic resin composite material and the wet heat environment performance retention rate are improved, and the continuous sizing treatment is suitable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waterborne polyimide sizing preparation technology, specifically relating to a modified carbon fiber with a surface-loaded polyimide interface layer, its preparation method, and its application. Background Technology

[0002] Carbon fiber possesses excellent properties such as high specific strength, high specific modulus, corrosion resistance, and thermal and electrical conductivity, making it an important reinforcing material in aerospace, rail transportation, new energy vehicles, and high-end equipment. However, carbon fiber surfaces are typically inert and have low surface energy, making bare fibers prone to fuzzing and breakage during processing, and exhibiting insufficient interfacial bonding with high-performance thermoplastic resin matrices. Therefore, sizing treatment is usually required to improve the bundle structure, abrasion resistance, and interfacial compatibility of carbon fibers.

[0003] Waterborne polyimide sizing agents possess advantages such as heat resistance, compatibility with high-temperature thermoplastic resins, and low volatile organic compound emissions, making them suitable for the preparation of high-performance thermoplastic resin composites such as polyetheretherketone, polyphenylene sulfide, thermoplastic polyimide, and polyetherimide. Waterborne polyimide sizing systems typically achieve waterborne delivery in the form of waterborne polyamic acid salts, which are then converted into a polyimide interfacial layer during subsequent heat treatment.

[0004] Current processes mostly employ a one-step treatment method involving direct drying and thermal imidization after sizing with water-based polyamic acid salts. During this process, several simultaneous events occur: moisture evaporation, residual organic solvent evaporation, organic amine counterion migration or release, carboxylate conversion, polyamic acid cyclization and dehydration, and film formation from the sizing layer. Because the sizing layer retains some water solubility and ionicity in the initial heating stage, it is prone to flow, migration, and localized enrichment. Simultaneously, the escape of small molecules and water vapor from the coating interior can easily cause defects such as micropores, bubbles, cracks, and uneven thickness. These defects reduce the interfacial bonding strength between carbon fibers and thermoplastic resins and affect the performance retention of the composite material under humid and hot environments.

[0005] Existing technologies primarily improve film quality by controlling the formulation of waterborne polyamic acid salts and adjusting the drying or imidization temperature program. However, these methods do not effectively separate the waterborne transport, interface fixation, and thermal imidization processes, and are also unable to avoid interfacial defects caused by the migration of the sizing layer during the initial heating stage and the simultaneous escape of small molecules. Therefore, it is necessary to provide a process for in-situ proton exchange and pre-curing after the polyamic acid salt sizing layer has formed on the carbon fiber surface and before thermal imidization, in order to improve the density and stability of the polyimide interfacial layer. Summary of the Invention

[0006] The purpose of this invention is to address the problems of coating migration, micropore and crack formation, high organic amine salt residue, and insufficient hydrothermal stability that easily occur during the direct thermal imidization of existing aqueous polyamic acid sizing layers. This invention provides a modified carbon fiber with a surface-loaded polyimide interface layer, its preparation method, and its applications. The method involves forming an aqueous polyamic acid sizing layer on the carbon fiber surface; before thermal imidization, the PAAS sizing layer is contacted with an aqueous solution of volatile organic acid or its vapor, resulting in in-situ proton exchange, converting at least a portion of the PAAS into water-insoluble polyamic acid (PAA), forming a pre-fixed PAA layer; low-temperature drying reduces free moisture, residual volatile organic acids, organic amine salts, and migratable small molecules; and segmented thermal imidization forms the polyimide (PI) interface layer. This invention achieves synergistic control of in-situ proton exchange, pre-fixation, and subsequent thermal imidization of the polyamic acid sizing layer. This modified carbon fiber can be used to prepare high-performance thermoplastic carbon fiber reinforced resin matrix composites (CFRTP).

[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention first provides a method for preparing modified carbon fibers with a surface-loaded polyimide interface layer, comprising the following steps: Step (1): A water-based polyamic acid sizing layer is formed on the surface of carbon fiber to obtain carbon fiber loaded with polyamic acid layer; Step (2): The polyamate layer obtained in step (1) is brought into contact with volatile organic acid, and an in-situ proton exchange reaction occurs on the carbon fiber surface, which converts part of the polyamate into water-insoluble polyamic acid, thereby forming a pre-fixed polyamic acid layer. Step (3): Dry the carbon fibers after acid treatment in step (2) to form a stable pre-fixed polyamic acid layer; Step (4): The carbon fibers dried in step (3) are subjected to segmented heating and thermal imidization treatment to convert the polyamic acid layer into a polyimide interface layer, thereby obtaining modified carbon fibers with a surface-loaded polyimide interface layer.

[0008] Preferably, the solid content of the aqueous polyamic acid sizing agent in step (1) is 0.1 wt% to 1.0 wt%.

[0009] Preferably, the aqueous polyamic acid salt in step (1) is prepared by low-temperature polycondensation of 3,3-dimethyl-4,4-diaminodicyclohexylmethane and pyromellitic dianhydride to obtain polyamic acid, followed by neutralization with an organic base and water inversion.

[0010] Preferably, the volatile organic acid in step (2) is selected from one or more of acetic acid, formic acid, propionic acid, butyric acid or trifluoroacetic acid.

[0011] Preferably, the contact method in step (2) includes immersion treatment with volatile organic acid aqueous solution or fumigation treatment with volatile organic acid vapor.

[0012] Preferably, the fumigation treatment using volatile organic acid vapor specifically involves placing the carbon fiber loaded with the polyamic acid layer in a sealed container and fumigating it with acid vapor generated by the volatile organic acid aqueous solution. The fumigation temperature is from room temperature to 60°C, and the fumigation time is 5 to 30 minutes.

[0013] Preferably, the organic acid aqueous solution has a mass fraction of 0.5 wt% to 5.0 wt%.

[0014] Preferably, the segmented heating and imidization treatment in step (4) includes: heating to 80°C at 1~3°C / min and holding for 30~60 min, then heating to 120°C at 1~3°C / min and holding for 20~40 min, then heating to 200°C at 2~4°C / min and holding for 20~40 min, and finally heating to 280~320°C at 2~4°C / min and holding for 30~90 min.

[0015] The present invention also provides modified carbon fibers with a surface-loaded polyimide interface layer obtained by the above preparation method.

[0016] The present invention also provides the application of modified carbon fibers with the above-described surface-loaded polyimide interface layer in thermoplastic carbon fiber composites.

[0017] Beneficial effects of the present invention 1. This invention forms an aqueous polyamic acid salt (PAAS) sizing layer on the surface of carbon fibers. Before thermal imidization, the PAAS sizing layer is contacted with an aqueous solution of volatile organic acids or their vapors, resulting in in-situ proton exchange, which converts at least part of the PAAS into water-insoluble polyamic acid (PAA), forming a pre-fixed PAA layer. Low-temperature drying reduces free water, residual volatile organic acids, organic amine salts, and migratable small molecules. Then, segmented thermal imidization is performed to form a polyimide (PI) interface layer. This decouples the aqueous transport of the aqueous polyamic acid salt, the in-situ fixation on the carbon fiber surface, and the thermal imidization process, avoiding significant migration of the aqueous polyamic acid salt sizing layer in the initial stage of heating due to its continued water solubility and ionicity.

[0018] 2. In this invention, before thermal imidization, in-situ proton exchange is induced by volatile organic acids, which converts at least part of the polyamic acid salt into water-insoluble polyamic acid, thereby pre-fixing the sizing layer. This helps to reduce defects such as pores, bubbles, cracks and uneven thickness during subsequent heat treatment.

[0019] 3. This invention uses volatile organic acids as treatment reagents. Compared with non-volatile acid treatment, it can reduce the residue of acids and their salts in subsequent drying and heat treatment processes, which is beneficial to reduce the hygroscopicity of the interface layer and improve the performance retention rate under humid and hot conditions.

[0020] 4. The acid treatment process of the present invention can significantly improve the mechanical strength, hydrophobicity and resistance to humid heat aging of sized carbon fibers after modification.

[0021] 5. The process of this invention uses water as the main medium, is simple to operate, has low equipment requirements, and can be connected with existing carbon fiber sizing, drying and heat treatment processes, and has the potential for continuous and industrial applications. Attached Figure Description

[0022] Figure 1 These are SEM images of the polyimide films treated with different concentrations of acetic acid according to the present invention. Figure 2 SEM images of the surface microstructure of carbon fibers after treatment with different concentrations of acetic acid according to the present invention. Figure 3 AFM images of the surface microstructure of carbon fibers after untreated and high-concentration acetic acid treatment according to the present invention; Figure 4 Test results of water contact angle of polyimide film under different treatment methods according to the present invention. Detailed Implementation

[0023] This invention first provides a method for preparing modified carbon fibers with a surface-loaded polyimide interface layer, comprising the following steps: Step (1): Forming an aqueous polyamic acid sizing layer on the carbon fiber surface, specifically: immersing the carbon fiber in an aqueous polyamic acid sizing agent working solution, preferably at room temperature for 1-3 minutes, to obtain carbon fiber loaded with a polyamic acid layer; the carbon fiber described in this invention is preferably T300 type polyacrylonitrile-based carbon fiber, and can also be applied to other industrial-grade continuous filament carbon fibers of the same series such as T700 and T800. It is preferred to perform desizing treatment before sizing, wherein the desizing treatment is to place the carbon fiber in a tube furnace and treat it at a constant temperature of 590-600 ℃ for 3-10 minutes to remove the original sizing agent on the surface; The aqueous polyamic acid salt is obtained by neutralizing polyamic acid with an organic amine or ammonia to form a salt and then adding water for phase inversion. Specifically, it is preferably prepared by low-temperature polycondensation of 3,3-dimethyl-4,4-diaminodicyclohexylmethane and pyromellitic dianhydride to obtain polyamic acid, followed by neutralization with an organic base and phase inversion with water. The low-temperature polycondensation temperature is preferably 0-10°C, and the time is preferably 4-8 hours. The organic base is preferably triethylamine, diethanolamine, or ammonia. The molar ratio of 3,3-dimethyl-4,4-diaminodicyclohexylmethane to pyromellitic dianhydride is preferably (0.98-1.02):1, and the molar ratio of the organic base to the carboxyl groups in the polyamic acid is preferably (1.0-1.2):1. The solid content of the aqueous polyamic acid salt sizing agent is preferably 0.1 wt%-1.0 wt%.

[0024] Step (2): The polyamate layer obtained in step (1) is brought into contact with volatile organic acid, and an in-situ proton exchange reaction occurs on the carbon fiber surface, which converts part of the polyamate into water-insoluble polyamic acid, thereby forming a pre-fixed polyamic acid layer. The volatile organic acid is preferably selected from one or more of acetic acid, formic acid, propionic acid, butyric acid, and trifluoroacetic acid, and does not contain non-volatile organic acids such as citric acid and oxalic acid. It is more preferably acetic acid. The mass fraction of the organic acid aqueous solution is preferably 0.5 wt% to 5.0 wt%. When the volatile organic acid is acetic acid, the mass fraction of the acetic acid aqueous solution is preferably 0.05 wt% to 1 wt%, more preferably 0.06 wt% to 0.3 wt%, and most preferably 0.2 wt%. When the acetic acid concentration is too low, the proton exchange rate is insufficient, and the pre-fixation effect of the coating layer is limited. When the acetic acid concentration is too high, the proton exchange rate is too fast, and polyamic acid may precipitate disorderly, resulting in a rough, loose, or cracked coating. When the volatile organic acid is formic acid, the mass fraction of the formic acid aqueous solution is preferably 0.1 wt% to 0.5 wt%; when the volatile organic acid is propionic acid or butyric acid, the mass fraction of its aqueous solution is preferably 0.1 wt% to 0.8 wt%; when the volatile organic acid is trifluoroacetic acid, the mass fraction of the trifluoroacetic acid aqueous solution is preferably 0.05 wt% to 1 wt%, more preferably 0.06 wt% to 0.3 wt%.

[0025] The contact methods include immersion treatment with a volatile organic acid aqueous solution or fumigation treatment with a volatile organic acid vapor. For immersion treatment with a volatile organic acid aqueous solution, the immersion temperature is preferably room temperature, and the immersion time is preferably 1-3 minutes. For fumigation treatment with a volatile organic acid vapor, the carbon fibers loaded with a polyamate layer are placed in a sealed container, and fumigated using acid vapor generated from a volatile organic acid aqueous solution. The fumigation temperature is preferably room temperature to 60°C, and the fumigation time is 5-30 minutes. This treatment method facilitates uniform penetration of acid vapor into the fiber bundle and is suitable for large-tow carbon fibers or continuous processing. The volatile organic acid vapor is generated from a volatile organic acid aqueous solution with a mass fraction of 0.5 wt% to 5.0 wt%.

[0026] Step (3): Dry the carbon fiber after acid treatment in step (2) to reduce free moisture, residual volatile organic acids, organic amine salts and migratable small molecules, and form a stable pre-fixed polyamic acid layer; the drying temperature is preferably 40~80 ℃ and the drying time is preferably 30~60 min.

[0027] Step (4): The carbon fibers dried in step (3) are subjected to segmented heating and thermal imidization treatment to convert the polyamic acid layer into a polyimide interface layer, thereby obtaining modified carbon fibers with a surface-loaded polyimide interface layer. The segmented heating and thermal imidization treatment preferably includes: heating to 80 ℃ at 1~3 ℃ / min and holding for 30~60 min, then heating to 120 ℃ at 1~3 ℃ / min and holding for 20~40 min, then heating to 200 ℃ at 2~4 ℃ / min and holding for 20~40 min, and finally heating to 280~320 ℃ at 2~4 ℃ / min and holding for 30~90 min.

[0028] The present invention also provides modified carbon fibers with a surface-loaded polyimide interface layer obtained by the above preparation method.

[0029] This invention also provides the application of modified carbon fibers with the above-described surface-loaded polyimide interface layer in thermoplastic carbon fiber composites. In the thermoplastic carbon fiber composite, the thermoplastic resin is preferably one of polyetheretherketone, polyphenylene sulfide, thermoplastic polyimide, or polyetherimide. In the composite, the preferred mass ratio of the modified carbon fibers with the surface-loaded polyimide interface layer to the thermoplastic resin is (0.3~1.2):1.

[0030] The present invention will be further described below with reference to embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Equivalent adjustments made by those skilled in the art to raw materials, concentrations, processing times, temperatures, and equipment types without departing from the concept of the present invention should all fall within the scope of protection of the present invention.

[0031] All raw materials used in the examples are commercially available. Unless otherwise stated, all percentages are by mass.

[0032] Example 1 A method for preparing modified carbon fibers with a surface-loaded polyimide interface layer includes the following steps: (1) Place commercially available carbon fiber bundles in a tube furnace and treat them at a constant temperature of 590 °C for 5 min to remove the original epoxy sizing agent on the surface, and obtain clean bare carbon fibers, which are then placed in a desiccator for later use.

[0033] (2) In a low-temperature ice-water bath at 0~5 ℃, high-purity nitrogen gas was continuously introduced into a three-necked flask equipped with a magnetic stirrer, a nitrogen delivery tube and a dropping funnel for protection. First, 10 mmol of 3,3-dimethyl-4,4-diaminodicyclohexylmethane was dissolved in 20 mL of N,N-dimethylacetamide. Then, 10 mmol of N,N-dimethylacetamide suspension of pyromellitic dianhydride was slowly added to the diamine solution. Polymerization was carried out for 4 h to obtain a polyamic acid solution. 11 mmol of triethylamine was added to neutralize and form a salt. Water was then added to dilute the solution to a solid content of 0.3 wt% to obtain an aqueous polyamic acid sizing agent working solution.

[0034] (3) Immerse the desized carbon fiber in the working solution of the aqueous polyamic acid sizing agent and soak at room temperature for 2 minutes. After taking it out, gently absorb the excess slurry to obtain carbon fiber loaded with polyamic acid layer.

[0035] (4) The carbon fiber loaded with polyamic acid salt layer was immersed in 0.2 wt% acetic acid aqueous solution at a bath ratio of 1:75 and immersed for 2 min at room temperature to carry out in-situ proton exchange reaction. After removal, excess acid liquid on the surface was gently absorbed.

[0036] (5) Place the acid-treated carbon fiber in a forced-air drying oven and pre-dry it at 60 °C for 45 min to reduce free moisture, residual volatile organic acids, organic amine salts and migratable small molecules.

[0037] (6) The pre-dried carbon fibers were placed in a muffle furnace and subjected to segmented thermal imidization according to the following procedure: the temperature was increased from room temperature to 80 ℃ at a rate of 2 ℃ / min and held for 45 min; then increased to 120 ℃ at a rate of 2 ℃ / min and held for 30 min; then increased to 200 ℃ at a rate of 3 ℃ / min and held for 30 min; finally increased to 300 ℃ at a rate of 3 ℃ / min and held for 60 min. The carbon fibers were then allowed to cool naturally to room temperature to obtain modified carbon fibers with a dense polyimide interface layer loaded on the surface.

[0038] Example 2 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that step (4) is changed to: immersing the sized carbon fiber in an aqueous solution of acetic acid with a mass fraction of 0.05 wt% and performing an in-situ proton exchange reaction at room temperature for 2 min.

[0039] Example 3 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that in step (4), the sized carbon fiber is suspended in a sealed fumigation container, the bottom of the container is filled with an aqueous solution of acetic acid with a mass fraction of 2.0 wt%, heated to 50 ℃, and fumigated for 20 min by the acetic acid vapor generated by natural volatilization.

[0040] Example 4 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that step (4) is changed to: immersing the sized carbon fiber in a 0.3 wt% formic acid aqueous solution and performing an in-situ proton exchange reaction at room temperature for 2 min.

[0041] Example 5 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that step (4) is changed to: immersing the sized carbon fiber in a 0.2 wt% trifluoroacetic acid aqueous solution and performing an in-situ proton exchange reaction at room temperature for 2 min.

[0042] Comparative Example 1 (1)~(3) are the same as steps (1)~(3) in Example 1, except that step (4) is omitted, acid treatment is not performed, and the sized carbon fiber is directly pre-dried and segmented thermal imidized according to steps (5)~(6) in Example 1.

[0043] Comparative Example 2 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that in step (4), the sized carbon fiber is immersed in an aqueous solution of acetic acid with a mass fraction of 1.0 wt%, and the in-situ proton exchange reaction is carried out at room temperature for 2 min.

[0044] Comparative Example 3 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that in step (4), the sized carbon fiber is immersed in an aqueous solution of acetic acid with a mass fraction of 0.5 wt%, and the in-situ proton exchange reaction is carried out at room temperature for 2 min.

[0045] Comparative Example 4 Steps (1) to (3) and (5) to (6) are the same as in Example 1, except that in step (4), the sized carbon fiber is immersed in a 0.2 wt% citric acid aqueous solution and the in-situ proton exchange reaction is carried out at room temperature for 2 min.

[0046] The morphology, wettability, thermal stability, single filament tensile strength, and interfacial properties of the modified carbon fibers and corresponding polyimide films prepared in each embodiment and comparative example were characterized.

[0047] (1) Surface morphology (SEM) Figure 1 SEM images of polyimide films treated with different concentrations of acetic acid are shown. Figure 1 a represents Example 2; Figure 1 b represents Example 1; Figure 1 c represents comparative example 3; Figure 1 d represents comparative example 2; Figure 1 e represents Comparative Example 1. It can be seen that the film surface of the Example is smooth and dense, with no obvious cracks or pores. In particular, the surface of Example 1 is more uniform, without fine lines, and smoother overall. The overall morphology of Example 1 is better than that of Example 2. The film surface of the comparative example shows obvious cracks and loose particles. In summary, it shows that 0.2% acetic acid treatment can obtain a dense polyimide coating.

[0048] Figure 2 SEM images of carbon fiber surfaces under different treatment conditions are shown. Figure 2 'a' represents Example 1, and it can be seen that the coating on the carbon fiber surface is uniform and continuous; as shown in Example 1... Figure 2 d represents Comparative Example 1, which shows that the coating on the fiber surface is discontinuous, with granular protrusions and fiber adhesion; for example Figure 2 c represents comparative example 2, which shows that the fiber surface coating is rough, loose, and uneven in thickness. For example... Figure 2 b represents Comparative Example 3. It can be seen that a sizing coating exists on the carbon fiber surface, but the coating uniformity and smoothness are weaker than in Example 1, with higher surface roughness and generally less overall coating continuity. Compared to the comparative example treated with high-concentration acid, it has fewer defects, but it is not as dense and smooth as the sample modified with suitable organic acid. The results indicate that treatment with a suitable concentration of volatile organic acid is an important factor in obtaining a uniform interface layer.

[0049] (2) Surface roughness (AFM) Figure 3 AFM images of the surface microstructure of carbon fibers after untreated and high-concentration acetic acid treatment according to this invention; wherein Figure 3 'a' represents Example 1; Figure 3 b represents Example 2; Figure 3c represents Comparative Example 1. As can be seen, compared with the untreated comparative example, the example treated with acetic acid impregnation showed no obvious local protrusions on the carbon fiber surface, the coating was continuous and complete overall, and there were fewer severe interface defects. This indicates that direct imidization after carbon fiber sizing will produce inherent protrusion defects, while acetic acid impregnation pretreatment can regulate the proton exchange rate, alleviate the problem of concentrated protrusions caused by disordered precipitation of polyamic acid, and effectively improve the overall uniformity of the fiber surface coating. However, high concentration of acetic acid will still cause the coating to be rough, cracked, and have particle protrusions. Acid treatment at this concentration alone cannot obtain a perfectly uniform and dense interface layer.

[0050] (3) Contact angle test Figure 4 This invention presents water contact angle test images of polyimide films under different processing methods. Specifically, the polyimide film is prepared by polymerizing dianhydride and diamine monomers to generate liquid polyamic acid (PAA), coating the PAA onto a substrate, heating for dehydration and imidization, and curing to form a smooth, solid PI film. To eliminate interference from the roughness and fiber morphology of the carbon fiber substrate and improve the accuracy of the contact angle test data, this test uses a pure flat PI film without a carbon fiber substrate instead of a thin interfacial coating on the carbon fiber surface for characterization. Wherein: Figure 4 a represents the PI film corresponding to Example 1. Figure 4 b represents the PI film corresponding to Example 3. Figure 4 c represents the PI film corresponding to Comparative Example 4. Figure 4 d represents the PI film corresponding to Example 2. Figure 4 e represents the PI film corresponding to Comparative Example 3. Figure 4 f represents the PI film corresponding to Comparative Example 1. Figure 4 g represents the PI film corresponding to Comparative Example 2. Taking the water contact angle test of the polyimide film treated with acetic acid as an example: when the acetic acid concentration increases within the range of 0.05% to 0.2%, the film contact angle increases and hydrophobicity is enhanced; however, when the concentration increases to 0.5% and 1.0%, the contact angle decreases, and the contact angle at a concentration of 1.0% is even lower than that of the untreated sample. Combined with SEM morphology and Wenzel model analysis, excessively high acid concentrations cause the proton exchange reaction to be too vigorous, resulting in discontinuous sizing layers, increased film surface roughness and defects, enhanced hydrophilicity, and decreased contact angle; appropriate acid concentration treatment can reduce film surface roughness and improve hydrophobicity. The water contact angles of all embodiments of this invention are higher than those of the comparative examples, indicating that the in-situ proton exchange process using suitable volatile organic acids in this invention can form a dense and smooth coating with superior hydrophobicity and resistance to damp heat. In contrast, the coatings of the comparative examples without acid treatment, with high-concentration acid treatment, or with non-volatile acid treatment have more defects, stronger hydrophilicity, and poor damp heat stability.

[0051] (4) Tensile strength of monofilament The tensile strength of carbon fiber monofilaments was tested using an electronic universal testing machine. 35 valid samples were tested in each group. The Weibull statistical analysis results are shown in Table 2.

[0052] Table 1 Tensile strength of carbon fiber monofilaments under different treatment conditions

[0053] The tensile strength of carbon fiber monofilaments in all embodiments in Table 1 is superior to that of the comparative examples. Among them, the tensile strength of Example 1 is the best, indicating that the volatile organic acid proton exchange process under the limited conditions of the present invention can completely protect the integrity of the carbon fiber surface coating and effectively improve the fiber mechanical strength and strength uniformity. Excessive concentration of acid, non-volatile acid or no proton exchange treatment will damage the interface layer and reduce the mechanical properties of carbon fiber.

[0054] (5) Composite material interface properties The modified carbon fibers prepared in each example and comparative example were combined with polyetheretherketone (PEEK) resin (where the mass ratio of modified carbon fibers to PEEK was 4:6) to prepare unidirectional composite materials. The interlaminar shear strength (ILSS) and the strength retention rate after damp heat aging were tested. The damp heat aging conditions were 85 ℃ / 85%RH environment for 96 h. The results are shown in Table 3.

[0055] Table 2. Interfacial properties of modified carbon fiber / PEEK composites

[0056] In Table 2, the interlaminar shear strength and damp heat aging strength retention rates of the composite materials in all the embodiments are better than those in the comparative examples. The overall performance of Example 1 is the best, indicating that the in-situ proton exchange pre-curing process of the present invention can construct a stable and dense interface layer, which greatly improves the interfacial bonding ability between carbon fiber and thermoplastic resin and the performance stability under damp heat environment. Acid-free treatment, high-concentration acid, and non-volatile acid treatment will degrade the interfacial performance and damp heat resistance of the composite material.

[0057] Based on the above results, using an appropriate concentration of volatile organic acid, especially 0.2 wt% acetic acid, for in-situ proton exchange and pre-curing after waterborne polyamic acid sizing and before thermal imidization can effectively improve the density and continuity of the polyimide interface layer, and enhance the interfacial properties and hygrothermal stability of carbon fibers and their thermoplastic composites.

[0058] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. All equivalent substitutions, combinations, or improvements made based on the technical concept of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing modified carbon fibers with a surface-loaded polyimide interface layer, characterized in that, Includes the following steps: Step (1): A water-based polyamic acid sizing layer is formed on the surface of carbon fiber to obtain carbon fiber loaded with polyamic acid layer; Step (2): The polyamate layer obtained in step (1) is brought into contact with volatile organic acid, and an in-situ proton exchange reaction occurs on the carbon fiber surface, which converts part of the polyamate into water-insoluble polyamic acid, thereby forming a pre-fixed polyamic acid layer. Step (3): Dry the carbon fibers after acid treatment in step (2) to form a stable pre-fixed polyamic acid layer; Step (4): The carbon fibers dried in step (3) are subjected to segmented heating and thermal imidization treatment to convert the polyamic acid layer into a polyimide interface layer, thereby obtaining modified carbon fibers with a surface-loaded polyimide interface layer.

2. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The solid content of the waterborne polyamic acid sizing agent in step (1) is 0.1 wt%~1.0 wt%.

3. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The aqueous polyamic acid salt described in step (1) is prepared by low-temperature polycondensation of 3,3-dimethyl-4,4-diaminodicyclohexylmethane and pyromellitic dianhydride to obtain polyamic acid, followed by neutralization with an organic base and water inversion.

4. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The volatile organic acid in step (2) is selected from one or more of acetic acid, formic acid, propionic acid, butyric acid or trifluoroacetic acid.

5. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The contact method in step (2) includes immersion treatment with volatile organic acid aqueous solution or fumigation treatment with volatile organic acid vapor.

6. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 5, characterized in that, The fumigation treatment using volatile organic acid vapors is as follows: carbon fibers loaded with polyamic acid salt layers are placed in a sealed container and fumigated using acid vapors generated by a volatile organic acid aqueous solution. The fumigation temperature is from room temperature to 60 ℃, and the fumigation time is 5~30 min.

7. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The organic acid aqueous solution has a mass fraction of 0.5 wt% to 5.0 wt%.

8. The method for preparing modified carbon fiber with a surface-loaded polyimide interface layer according to claim 1, characterized in that, The segmented heating and imidization treatment in step (4) includes: heating to 80 ℃ at 1~3 ℃ / min and holding for 30~60 min, then heating to 120 ℃ at 1~3 ℃ / min and holding for 20~40 min, then heating to 200 ℃ at 2~4 ℃ / min and holding for 20~40 min, and finally heating to 280~320 ℃ at 2~4 ℃ / min and holding for 30~90 min.

9. Modified carbon fibers with a surface-loaded polyimide interface layer obtained by the preparation method of claim 1.

10. The application of the modified carbon fiber with a surface-loaded polyimide interface layer as described in claim 9 in thermoplastic carbon fiber composites.